2022
DOI: 10.1186/s12889-022-13910-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the intersectionality of family SES and gender with psychosocial, behavioural and environmental correlates of physical activity in Dutch adolescents: a cross-sectional study

Abstract: Background Examining the correlates of adolescent’s physical activity (PA) and how they may differ according to the intersection of gender and family socioeconomic status (SES) can support the development of tailored interventions to more effectively promote adolescents’ PA. This study explored how the associations between psychosocial, behavioural and environmental factors and adolescent’s PA differed according to gender and family SES. Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Social media addiction (SMA), defined as prolonged exposure to and repeated use of social media [ 6 ], is characterized by a dysfunctional form of being unable to resist the motivation to follow social media, and experiencing distress if prohibited from using social media [ 7 ]. A meta-analysis of 64 countries demonstrated that the pooled prevalence rate of SMA was 17.42% in the general population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social media addiction (SMA), defined as prolonged exposure to and repeated use of social media [ 6 ], is characterized by a dysfunctional form of being unable to resist the motivation to follow social media, and experiencing distress if prohibited from using social media [ 7 ]. A meta-analysis of 64 countries demonstrated that the pooled prevalence rate of SMA was 17.42% in the general population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%